A nanoparticle type heavy oil viscosity reducer and its preparation method and application
By preparing nanoparticle heavy oil viscosity reducing agent, the surface effect and high specific surface area characteristics are used to solve the problem of poor contact of heavy oil viscosity reducing agent in the prior art, and the efficient viscosity reduction effect of heavy oil and the feasibility of industrial application are achieved.
Patent Information
- Application Number
- CN202411786508.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-06
AI Technical Summary
In the prior art, heavy oil viscosity reducing agent cannot fully and quickly contact the asphaltene molecules in heavy oil, resulting in poor viscosity reduction effect and efficiency.
A nanoparticle heavy oil viscosity reducing agent is used. The viscosity reducing agent is prepared from anhydrous citric acid, benzylamine and octadecamine by hydrothermal synthesis to form a polymer with carbon 18 long chain, benzyl and amide group functional groups. The surface effect and high specific surface area characteristics of the nanoparticles are used to promote the depolymerization of the viscosity reducing agent molecules with the asphaltene molecules in the heavy oil.
It achieves good viscosity reduction effect of heavy oil, significantly reduces the viscosity value of heavy oil, and has a simple process, environmental protection, low cost, and is suitable for industrial applications.
Smart Images

Figure CN119241835B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of heavy oil chemical additives, and in particular relates to a nano-particle type heavy oil viscosity reducer and a preparation method and application thereof. Background Art
[0002] Thick oil, also known as heavy oil, has the characteristics of large molecular weight, high viscosity and high density, which bring great difficulties to the mining and transportation of thick oil. For example, due to the high viscosity of thick oil, the fluidity is very poor, resulting in large seepage resistance of thick oil in the oil layer and inability to flow from the oil reservoir to the bottom of the well, making it difficult to mine. Thick oil contains a large number of colloid and asphaltene molecules. The colloid and asphaltene have large molecular weight and strong polarity. The intermolecular interaction shows a regular layered structure, which can easily form highly regular aggregates, with large internal friction, and shows the characteristics of high viscosity on a macro scale.
[0003] It is necessary to reduce the viscosity of heavy oil. In recent years, chemical viscosity reduction has been widely studied. Chemical viscosity reduction mainly includes emulsification viscosity reduction and oil-soluble viscosity reduction. The goal of oil-soluble viscosity reduction is to reduce the viscosity of heavy oil by using oil-soluble viscosity reducers. The principle is to use the interaction between viscosity reducer molecules and asphaltene molecules to disperse the asphaltene aggregate structure and cause the asphaltene aggregates to undergo irreversible depolymerization, thereby reducing the viscosity of heavy oil.
[0004] Since asphaltene molecules are tightly aggregated and have a regular structure, the viscosity reducers in the prior art have the problem of being unable to fully and quickly contact the asphaltene molecules, resulting in average viscosity reduction effect and efficiency. Summary of the invention
[0005] In view of this, the purpose of the embodiments of the present application is to provide a nanoparticle-type heavy oil viscosity reducer and its preparation method and application, so as to solve the general problems of viscosity reducing effect and viscosity reducing efficiency of viscosity reducers in the prior art. The heavy oil viscosity reducer provided in the embodiments of the present application forms a polymer with good viscosity reducing effect through molecular design, and due to its small molecular weight, it presents a nanoparticle form microscopically, and has good dispersibility and penetration ability based on the surface effect and high specific surface area of nanoparticles; it also promotes the depolymerization of asphaltene molecules in heavy oil by viscosity reducer molecules, showing a good viscosity reducing effect.
[0006] The embodiment of the present application is implemented as follows:
[0007] The present application provides a method for preparing a nanoparticle-type heavy oil viscosity reducer, comprising the following steps:
[0008] S1. In terms of molar ratio, weigh an appropriate amount of anhydrous citric acid, benzylamine and octadecylamine, dissolve them in an ethanol solution, and stir evenly; then place them in a reaction vessel, react at a constant temperature of 180°C, and cool to obtain a crude product;
[0009] S2. The crude product is concentrated and purified by dialysis, and then dried to obtain a nanoparticle-type heavy oil viscosity reducer.
[0010] Furthermore, the molar ratio of the anhydrous citric acid, the benzylamine and the octadecylamine is 1:(2-2.7):(0.3-1).
[0011] Furthermore, the molar ratio of the anhydrous citric acid, the benzylamine and the octadecylamine is 1:2:1.
[0012] Furthermore, the step S1 of stirring evenly specifically refers to stirring at a constant temperature of 30° C. for 0.5 to 1 h.
[0013] Furthermore, the reaction time of the constant temperature reaction at 180° C. in step S1 is 9 to 12 hours.
[0014] Furthermore, in step S2, the dialysate is a mixed solution of ethanol and deionized water.
[0015] The present application also provides a nanoparticle type heavy oil viscosity reducer, which is prepared by any of the above preparation methods. The nanoparticle type heavy oil viscosity reducer is specifically a polymer, which includes at least a carbon 18 long chain, a benzyl group and an amide group functional group, and can play a role in reducing the viscosity of heavy oil.
[0016] The present application also provides an application of a nanoparticle-type heavy oil viscosity reducer, specifically, the viscosity reducer obtained by the aforementioned preparation method or the aforementioned viscosity reducer is placed in the heavy oil, and after heating and stirring, the viscosity value of the heavy oil is significantly reduced; even without heating or stirring, the viscosity value of the heavy oil will also be reduced.
[0017] Furthermore, the mass volume ratio of the viscosity reducer to the heavy oil is (0.18-0.2) g:100 mL.
[0018] Compared with the prior art, the beneficial effects of this application are:
[0019] 1. The nano-sized small-particle heavy oil viscosity reducer provided by the present application has a stronger dispersing and penetrating ability based on the surface effect of high specific surface area, which can reduce the difficulty of migration of viscosity reducer molecules in heavy oil and asphaltene aggregates, and the viscosity reducer with small molecular weight can be dispersed and penetrated into the asphaltene molecules of heavy oil faster and more evenly. And the heavy oil viscosity reducer molecules introduce multi-site amide groups in the molecular structure, which can enhance the hydrogen bonding between the viscosity reducer and the heavy oil, and the benzyl groups on the molecules can reduce the interaction of the large π bonds between the asphaltene molecular layers, and promote the depolymerization of the asphaltene molecular aggregates; the carbon 18 long chain and the charged amide group can form a solubilizer based on the interaction between molecules to quickly and efficiently wrap the depolymerized asphaltene molecules, avoid the asphaltene molecules from continuing to agglomerate, and achieve the irreversible viscosity reduction of heavy oil. It has a good viscosity reduction effect.
[0020] 2. This application uses small organic molecules containing functional groups as raw materials and is prepared by hydrothermal synthesis. The process is simple and easy to control. No toxic solvents are used in the preparation process. It is more environmentally friendly and has lower cost, which is conducive to industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 This is the infrared spectrum of the nanoparticle-type heavy oil viscosity reducer provided in this application;
[0023] Figure 2 This is a scanning electron microscope image of heavy oil asphaltene that has not been treated with a viscosity reducer;
[0024] Figure 3 This is a scanning electron microscope image of heavy oil asphaltene treated with the nanoparticle-type heavy oil viscosity reducer provided by the present application;
[0025] Figure 4 Transmission electron microscope image of the nanoparticle-type heavy oil viscosity reducer provided for the application;
[0026] Figure 5 X-ray diffraction pattern of the nanoparticle-type heavy oil viscosity reducer provided in the application. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical scheme and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. The illustrative implementation methods and descriptions of the present application are only used to explain the present application and are not intended to limit the present application. Any product identical or similar to the present application that is obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.
[0028] The specific experimental steps or conditions not indicated in the embodiment can be carried out according to the operation or conditions of the conventional experimental steps described in the prior art in this area. The reagents used and other instruments that do not indicate the manufacturer are all conventional reagent products that can be obtained commercially. In addition, the accompanying drawings are only schematic diagrams of the embodiments of the present application and are not necessarily drawn to scale. The same reference numerals in the figure represent the same or similar parts, and thus their repeated description will be omitted. Some block diagrams shown in the accompanying drawings are functional entities and do not necessarily correspond to physically or logically independent entities.
[0029] The present application provides a nanoparticle-type heavy oil viscosity reducer, which is specifically one or more polymers. The polymer includes at least a carbon 18 long chain, a benzyl group, and an amide group. These functional groups can interact with the asphaltene molecules in the heavy oil, promote the depolymerization of the asphaltene molecules, and thus reduce the viscosity of the heavy oil. Specifically, the introduction of multi-site amide groups in the molecular structure can enhance the hydrogen bonding between the viscosity reducer and the heavy oil, and the benzyl group can reduce the interaction between the large π bonds between the asphaltene molecular layers, and promote the depolymerization of the asphaltene molecular agglomerates; the carbon 18 long chain and the charged amide group can form a solubilizer based on the interaction between molecules to quickly and efficiently wrap the depolymerized asphaltene molecules, avoid the asphaltene molecules from continuing to agglomerate, and achieve irreversible viscosity reduction of the heavy oil. It has a good viscosity reduction effect.
[0030] The nanoparticle type heavy oil viscosity reducer is prepared by hydrothermal synthesis using anhydrous citric acid, benzylamine and octadecylamine. The amount of anhydrous citric acid, benzylamine and octadecylamine, in terms of molar ratio, is preferably 1: (2-2.7): (0.3-1), and more preferably 1:2:1.
[0031] The present application also provides a method for preparing a nanoparticle type heavy oil viscosity reducer. Specifically, an appropriate amount of anhydrous citric acid, benzylamine and octadecylamine are weighed and dissolved in an ethanol solution, and stirred to make the raw materials fully mixed and evenly dispersed, preferably at a constant temperature of 30°C for 0.5 to 1h. Then the mixed solution is placed in a reactor, and the reaction is carried out at a constant temperature of 180°C, and the reaction time is preferably 9 to 12 hours, and the crude product is cooled to room temperature to obtain a crude product. The crude product is concentrated using a rotary evaporator and then dialyzed for purification, and the nanoparticle type heavy oil viscosity reducer is obtained after vacuum drying.
[0032] The reactor is preferably a high-temperature and high-pressure reactor equipped with a polytetrafluoroethylene liner, which has high chemical and thermal stability and a very low friction coefficient, and can ensure the smooth progress of the reaction and reduce the error caused by the material hanging on the wall. The crude product is dialyzed using a mixed solution of ethanol and deionized water, and the dialysis time is preferably 3 days to fully remove the impurities in the product.
[0033] The present application also provides an application of a nano-particle type heavy oil viscosity reducer in treating heavy oil, specifically adding the nano-particle type heavy oil viscosity reducer provided by the present application to the heavy oil, and the viscosity reducer molecules are dispersed and penetrated into the heavy oil asphaltene molecules, so that the layered asphaltene is irreversibly depolymerized into fragments. After the viscosity reducer is added to the heavy oil, the heavy oil is preferably heated and stirred, and the temperature is raised to 50°C and kept constant for half an hour. Heating and stirring the heavy oil can make the asphaltene molecules and the viscosity reducer molecules contact faster and more fully based on the molecular thermal diffusion effect and mass transfer effect, so that the viscosity reduction effect is more efficient. In practical applications, it is limited by the application environment, such as places such as mine cracks that are inconvenient to stir or heat up, and it is also possible not to heat up or stir, but to place the viscosity reducer in the heavy oil as evenly as possible. The viscosity reducer provided by the present application has a nano effect, a high specific surface area and a good surface effect, and can also diffuse and penetrate into the asphaltene. It’s just that compared with artificially accelerating molecular contact methods such as heating or stirring, the viscosity reduction effect is slower, but it still has a good viscosity reduction effect.
[0034] The acidification retarder and the retarding acid solution provided in the present application will be further described below in conjunction with the embodiments.
[0035] Embodiment 1:
[0036] Weigh 2.8818g of anhydrous citric acid, 2.8931g of benzylamine, and 4.8512g of octadecylamine in 200mL of ethanol solution and stir at 30°C for 0.5h. Then place the mixed solution in a high-temperature and high-pressure reactor, react at 180°C for 10h, and then cool to room temperature to obtain a crude product. Use a rotary evaporator to concentrate the crude product, then place it in a dialysis bag and dialyze it with a mixed solution of ethanol and deionized water for 3 days to obtain a solid, which is then placed in a vacuum oven and dried at 55°C for 10h to obtain a finished viscosity reducer.
[0037] Embodiment 2:
[0038] Weigh 3.8424g of anhydrous citric acid, 5.7861g of benzylamine, and 1.6171g of octadecylamine in 200mL of ethanol solution and stir at 30°C for 1h. Then place the mixed solution in a high temperature and high pressure reactor, react at 180°C for 12h, and then cool to room temperature to obtain a crude product. Use a rotary evaporator to concentrate the crude product, then place it in a dialysis bag and dialyze it with a mixed solution of ethanol and deionized water for 3 days to obtain a solid, which is then placed in a vacuum oven and dried at 55°C for 10h to obtain a finished viscosity reducer.
[0039] Embodiment 3:
[0040] Weigh 3.8424 g of anhydrous citric acid, 4.9289 g of benzylamine, and 3.7730 g of octadecylamine in 200 mL of ethanol solution and stir at 30 ° C for 1 hour. Then place the mixed solution in a high temperature and high pressure reactor, react at 180 ° C for 12 hours, and then cool to room temperature to obtain a crude product. Use a rotary evaporator to concentrate the crude product, then place it in a dialysis bag and dialyze it with a mixed solution of ethanol and deionized water for 3 days to obtain a solid, which is then placed in a vacuum oven at 55 ° C for 10 hours to obtain a finished viscosity reducer.
[0041] Embodiment 4:
[0042] Weigh 3.8424g of anhydrous citric acid, 5.3575g of benzylamine, and 2.6951g of octadecylamine in 200mL of ethanol solution and stir at 30°C for 1h. Then place the mixed solution in a high temperature and high pressure reactor, react at 180°C for 12h, and then cool to room temperature to obtain a crude product. Use a rotary evaporator to concentrate the crude product, then place it in a dialysis bag and dialyze it with a mixed solution of ethanol and deionized water for 3 days to obtain a solid, which is then placed in a vacuum oven and dried at 55°C for 10h to obtain a finished viscosity reducer.
[0043] Embodiment 5:
[0044] Weigh 3.8424g of anhydrous citric acid, 5.3575g of benzylamine, and 2.6951g of octadecylamine in 200mL of ethanol solution and stir at 30°C for 0.5h. Then place the mixed solution in a high-temperature and high-pressure reactor, react at 180°C for 9h, and then cool to room temperature to obtain a crude product. Use a rotary evaporator to concentrate the crude product, then place it in a dialysis bag and dialyze it with a mixed solution of ethanol and deionized water for 3 days to obtain a solid, which is then placed in a vacuum oven and dried at 55°C for 10h to obtain a finished viscosity reducer.
[0045] Embodiment 6:
[0046] Weigh 2.8818g of anhydrous citric acid, 3.2145g of benzylamine, and 4.0427g of octadecylamine in 200mL of ethanol solution and stir at 30°C for 0.5h. Then place the mixed solution in a high-temperature and high-pressure reactor, react at 180°C for 12h, and then cool to room temperature to obtain a crude product. Use a rotary evaporator to concentrate the crude product, then place it in a dialysis bag and dialyze it with a mixed solution of ethanol and deionized water for 3 days to obtain a solid, which is then placed in a vacuum oven at 55°C for 10h to obtain a finished viscosity reducer.
[0047] Embodiment 7:
[0048] Weigh 2.8818g of anhydrous citric acid, 3.2145g of benzylamine, and 4.0427g of octadecylamine in 200mL of ethanol solution and stir at 30°C for 1h. Then place the mixed solution in a high-temperature and high-pressure reactor, react at 180°C for 10h, and then cool to room temperature to obtain a crude product. Use a rotary evaporator to concentrate the crude product, then place it in a dialysis bag and dialyze it with a mixed solution of ethanol and deionized water for 3 days to obtain a solid, which is then placed in a vacuum oven and dried at 55°C for 10h to obtain a finished viscosity reducer.
[0049] The viscosity reducing effect of the viscosity reducers obtained in Examples 1 to 7 was tested, and the testing method was as follows: the first step: using a beaker to measure 100 mL of heavy oil and put it into a tall beaker, and 10 portions were prepared for standby; the second step: according to SY / T 0520-2008 "Determination of Crude Oil Viscosity by Rotational Viscometer Balance Method", 10 portions of heavy oil were heated by a constant temperature heating jacket, kept constant temperature at 50±0.1°C for 0.5 hour, and the apparent viscosity was measured by a NDJ-8S type rotational viscometer, and the arithmetic mean was taken for 3 measurements, which was recorded as V0; the third step: 0.1000 g of the viscosity reducers obtained in Examples 1 to 7 were respectively dissolved in 10 mL of toluene, and then the viscosity reducer solutions were respectively added to the heavy oil and stirred evenly, kept constant temperature at 50±0.1°C for 0.5 hour, and the apparent viscosity was measured by a NDJ-8S type rotational viscometer, and the arithmetic mean was taken for 3 measurements, which was recorded as V1.
[0050] The calculation formula of viscosity reduction rate is: ; Wherein, VRR is the viscosity reduction rate; V0 is the initial apparent viscosity of the heavy oil before viscosity reduction, V1 is the apparent viscosity of the heavy oil after viscosity reduction, and the viscosity unit is mPa·s.
[0051] The viscosity reducing agents obtained in Examples 1 to 7 were tested and calculated, and the viscosity reducing rate results are shown in the following table.
[0052] Table 1: Viscosity reduction results
[0053] sample Molar ratio of anhydrous citric acid, benzylamine and octadecylamine Viscosity reduction rate / % Example 1 1:1.8:1.2 39.86 Example 2 1:2.7:0.3 46.41 Example 3 1:2.3:0.7 46.15 Example 4 1:2.5:0.5 49.54 Example 5 1:2.5:0.5 51.08 Example 6 1:2:1 54.77 Example 7 1:2:1 55.08
[0054] It can be seen from the above table that when the molar ratio of anhydrous citric acid, benzylamine and octadecylamine is 1:2:1, the viscosity reduction rate is the largest and the viscosity reduction effect is the strongest.
[0055] In order to study the effect of viscosity reducer dosage on viscosity reduction effect, 0.0800g, 0.1200g, and 0.2000g of the viscosity reducer obtained in Example 7 were weighed and dissolved in 10mL toluene respectively, and the viscosity reduction effect test was carried out according to the same standard and steps to obtain the viscosity reduction rate. When the viscosity reducer dosage was 0.0800g, the viscosity reduction rate was 52.33%; when the viscosity reducer dosage was 0.1200g, the viscosity reduction rate was 57.14%; when the viscosity reducer dosage was 0.2000g, the viscosity reduction rate was 57.35%. It can be seen that the viscosity reducer as a whole shows the characteristics of increasing viscosity reduction rate with increasing dosage; when the viscosity reduction rate reaches the peak value, it no longer shows an increasing trend with increasing viscosity reducer dosage. From the principle analysis, more viscosity reducer molecules can more fully and quickly contact and depolymerize the asphaltene in the heavy oil, so a positive correlation between the viscosity reducer dosage and the viscosity reduction effect is shown. The dosage of viscosity reducer continues to increase. Since the interaction between viscosity reducer molecules and asphaltene molecules has reached a saturated state, the viscosity reduction effect of heavy oil no longer increases significantly, showing a stable viscosity reduction rate.
[0056] The structure and composition of the viscosity reducer obtained in Example 7 were determined by infrared spectrometer. Figure 1 As shown. Figure 1 It can be seen that at 1398cm -1 CN bond vibration occurs at 1542cm -1 The NH bond bending vibration appears at 1701cm -1 The carbonyl characteristic peak appeared at 698 cm -1 and 724cm -1 The benzene ring skeleton appeared at 3305cm -1 OH bond stretching vibration appears at the position, and there is no characteristic absorption peak of carboxyl -COOH in the figure, which means that the viscosity reducer molecule does not contain unpolymerized monomers. The infrared results show that the target viscosity reducer product is successfully obtained.
[0057] Figure 2 and Figure 3 The SEM images of heavy oil asphaltene before and after viscosity reduction are respectively Figure 2 It can be seen from the figure that before the treatment with the viscosity reducer, the asphaltene in the heavy oil presents a complete and dense layered stacking structure. Due to the presence of asphaltene, the initial viscosity of the heavy oil is very large, above 32000 mPa·s. After the heavy oil viscosity reducer provided in Example 7 of the present application is used for viscosity reduction treatment, the scanning electron microscope image of the asphaltene is as follows: Figure 3 As shown in the figure, it can be seen that the original dense and stable layered structure is depolymerized and split into several fragments; the fragmented asphaltene structure is dispersed and has many gaps between each other. Under the influence of the viscosity reducer, it disperses faster and the structure is no longer stable, which is manifested in a significant decrease in viscosity value on a macro scale.
[0058] Figure 4 The transmission electron microscope image of the heavy oil viscosity reducer provided by the present application is shown, from which it can be seen that under the 10nm size background, the heavy oil viscosity reducer appears in a uniform granular state. This proves that the synthesized viscosity reducer has a small molecular weight and is in a nanometer size, which facilitates the rapid dispersion and penetration of the viscosity reducer molecules into the heavy oil asphaltene; the particles of the same size and uniform distribution also prove the successful synthesis of the viscosity reducer, and there is no large molecule with a large molecular weight formed by intermolecular agglomeration, and there is no unsynthesized monomer substance.
[0059] Figure 5 The X-ray diffraction diagram of the heavy oil viscosity reducer provided by the present application is shown. The three curves CNPs-1, CNPs-2, and CNPs-3 in the figure are XRD characterizations of the heavy oil viscosity reducers obtained in the three groups of embodiments of Example 2, Example 4, and Example 6 respectively; the three curves have the same trend, and a broad peak representing amorphous carbon appears at about 22°, proving that the carbon nanoparticle heavy oil viscosity reducer synthesized in the present application meets the structural characteristics of amorphous carbon. Amorphous carbon has a very low degree of crystallization and a large specific surface area. The large specific surface area provides more contact surfaces and has the advantages of strong adsorption performance and high viscosity reduction rate.
[0060] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a nanoparticle-type heavy oil viscosity reducer, characterized in that: include: S1. In molar ratio, anhydrous citric acid, benzylamine and octadecylamine are dissolved in an ethanol solution and stirred; then placed in a reaction vessel, reacted at a constant temperature of 180 ° C, and cooled to obtain a crude product; the molar ratio of the anhydrous citric acid, the benzylamine and the octadecylamine is 1: (2 to 2.7): (0.3 to 1); S2. The crude product is concentrated and purified by dialysis, and then dried to obtain a nanoparticle-type heavy oil viscosity reducer.
2. The method for preparing the nanoparticle type heavy oil viscosity reducer according to claim 1, characterized in that: The molar ratio of the anhydrous citric acid, the benzylamine and the octadecylamine is 1:2:
1.
3. The method for preparing the nanoparticle type heavy oil viscosity reducer according to claim 1, characterized in that: The stirring method in step S1 is constant temperature stirring at 30° C. for 0.5 to 1 h.
4. The method for preparing the nanoparticle type heavy oil viscosity reducer according to claim 1, characterized in that: The reaction time in step S1 is 9 to 12 hours.
5. The method for preparing the nanoparticle type heavy oil viscosity reducer according to claim 1, characterized in that: The dialysate in step S2 is a mixed solution of ethanol and deionized water.
6. A nanoparticle-type heavy oil viscosity reducer, characterized in that: Prepared by the preparation method according to any one of claims 1 to 5.
7. The use of the nanoparticle type heavy oil viscosity reducer according to claim 6, characterized in that: The nano-particle type heavy oil viscosity reducer is placed in heavy oil to reduce the viscosity of the heavy oil.
8. The use of the nanoparticle type heavy oil viscosity reducer according to claim 7, characterized in that: The mass volume ratio of the nano-particle type heavy oil viscosity reducer to the heavy oil is (0.18-0.2) g:100 mL.
Citation Information
Patent Citations
Low-temperature-resistant viscosity reducer for oil exploitation and preparation method thereof
CN104449623A
Reversible Pickering emulsion, preparation method of reversible Pickering emulsion, and reversible high-temperature high-density drilling fluid
CN108841364A